Specific and common molecular alterations in knock outs of 3 desmosomal genes in HL1 cell model of Arrhythmogenic Cardiomyophathy. (10th June 2022) - Vallverdu-Prats, M; Brugada, R; Alcalde, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Obra Social "La Caixa Foundation" Introduction: Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is a heritable cardiac disease characterized by a progressive loss of myocardium and its replacement by fibrofatty tissue that predominantly affects the right ventricle (1, 2). Worldwide prevalence of ARVC is ranging from 1:1000 to 1:5000 (3, 4), and it is responsible for around 20% of all cases of sudden cardiac death (SCD) among people under 35 years of age (5). The main genetic cause are mutations in desmosomal genes (4). It is known that mutations in those genes could alter important molecular functions such as calcium homeostasis (6), and they also could cause important structural and electrical alterations such as fibrosis, adipogenesis, inflammation and arrhythmogenesis (7). We lack better understanding of those pathophysiological mechanisms and their relationship with the causal gene. Purpose: This study aims to elucidate molecular pathways triggered by genetic defects in three of the main genes in ARVC and determine common and gene-specific molecular features. Methods: Cardiac HL-1 cell line was edited by CRISPR/Cas9 to generate Knock Outs (KO) of three of the most frequent causal genes in ARVC: PKP2, DSG2 and DSC2. Expression levels of ARVC-related genes were tested by RT-PCR: desmosome, calcium handling and connexome related genes. Changes in the total amount of protein were checked by western blot using total protein lysate. Moreover, calcium transients were performed on all clones. Results: HL1 KO-PKP2 showed downregulation of SCN5A, CX43, RyR2, Atp2a2, Slc8a1, Casq2, ANK2, DSC2 DSG2 and DSP. HL1 KO-DSG2 showed a downregulation of ANK2, DSC2, CX43 and PG and HL1 KO-DSC2 clones presented a downregulation of CASQ2 and ANK2. Functionally, calcium transients showed significant differences in 10mM peak of caffeine in PKP2 but still not conclusive for DSC2 and DSG2 clones. Conclusions: Results suggest that pathophysiological mechanisms of ARVC are partially depending on the causal gene. Loss of function of PKP2 and DSC2 may be related to a dysregulation of calcium homeostasis and loss of function of DSG2 may cause alterations in connexome genes expression related to electrical dysfunction. Moreover, the absence of ANK2 expression in all HL1 cell lines might suggest a common molecular hallmark of ARVC in the presented cell model.